Immunization schedule in Ukraine: history of implementation and list of vaccines - Dorykevych, Kateryna; Kremin, Yuliia (Annals of Mechnikov’s Institute, 2024)
Introduction. Vaccination is a global health success story that saves millions of lives (WHO). Every year, thanks to it, it is possible to prevent 3.5-5 million deaths from such diseases as diphtheria, tetanus, whooping cough, influenza and measles. The purpose of our study was to conduct a comparative analysis of changes in the Immunization schedule of Ukraine for 1996-2022 and establish a list of registered vaccines in accordance with it. Material & methods. The research materials were the orders of the Ministry of Health of Ukraine and data from the State Register of Medicines of Ukraine. The method of data systematization, generalization and comparative analysis was used. Results & discussion. A study of the history of immunization schedule of Ukrainian for 1996-2022 showed that during this time the scheme of mandatory vaccination against measles did not change, but against tuberculosis, poliomyelitis, diphtheria, whooping cough, tetanus, epidemic parotitis and rubella – changed, mainly with regard to the timing of revaccination. Also, since 2011, vaccination against hepatitis B has been included in the immunization schedule . As of April 2024, 30 vaccines have been registered in Ukraine to ensure the vaccination calendar, the production of which involves 39 manufacturers from different countries, the largest of which are from Belgium and India (8 each, 20.5% each), France (6, 15.4%), Hungary (5, 12.8%) and Indonesia (4, 10.3%). The largest number of vaccines are produced by Sanofy (France, Hungary, Canada) (12 vaccines, 30.8%), GlaxoSmithKline Biologicals S.A., Belgium (8, 20.5%) and Serum Institute of India. Pvt. Ltd., India (7, 17.9%). Most vaccines (10, 33.3%) are intended for vaccination against one of the diseases (hepatitis B, tuberculosis, measles, poliomyelitis 1, 2, 3 types, poliomyelitis 1 and 3 types). Concliusions. Changes in immunization schedule of Ukraine for the period 1996 - 2022 mainly related to vaccination schemes against tuberculosis, poliomyelitis, diphtheria, whooping cough, tetanus, epidemic parotitis and rubella, and since 2011 vaccination against hepatitis B has been introduced as mandatory. The schedule provides for the prevention of 10 infectious diseases, while currently 30 relevant vaccines are registered in Ukraine. Keywords: vaccination, immunization schedule, vaccines